MORFOSINTAKSIS NOMINAL DAN KALA BAHASA SKOU - Yohanis Sanjoko (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2018)
AbstractSkow language is one of local language in Papua Province whose relatively less of speaker. This language is spoken by people who live in village of Skou Mabo, Skou Yambe, and Skou Sae. Skou language is used in border territory of Indonesia and Papua New Guinea. This writing uses descriptive method with three stages, namely, collecting data stage, analyzing data stage, and presenting the result of analysis data stage. The data, in this writing, was collected by using interview method (metode cakap) then analyzed by using equivalent method (metode padan).The result shows that phrase of number in Skou language is adverbial-clause. Pronoun of person in Skou language consists of three types, they are, first person pronoun, second person pronoun, and third person pronoun. Pronoun of person in Skou language influences verbal form and become dual-subject. Skou language marks its possessive pronoun by using word order. This language marks future tense only, and its marker using verb reduplication. Aspect marker of Skou language are reduplication, agree with person pronoun and its position is after verb. Skou language is a kind of language which periphrasticallymarks mood and tense.  AbstrakSalah satu bahasa daerah yang terdapat di Provinsi Papua dengan jumlah penutur yang kecil adalah bahasa Skou. Bahasa Skou dituturkan oleh masyarakat suku Skou yang tinggal di Kampung Skou Mabo, Kampung Skou Yambe, dan Kampung Skou Sae. Bahasa Skou terletak di wilayah perbatasan Indonesia dengan negara Papua Nugini. Tulisan ini mengunakan metode deskriptif dengan tiga tahapan, yaitu tahap penyediaan data, tahap analisis data, dan tahap penyajian hasil analisis data. Penyediaan data tulisan ini menggunakan metode cakap. Analisis data menggunakan metode padan. Hasil kajian menunjukkan bahwa frasa numeralia bahasa Skou bersifat adverbia-klausal. Pronomina persona bahasa Skou terdiri atas tiga pronomina persona, yaitu pronomina persona pertama, pronomina persona kedua, dan pronomina persona ketiga. Pronomina persona bahasa Skou memengaruhi bentuk verba dan menjadi dual-subjek. Bahasa Skou menandai kepemilikan dengan urutan kata. Bahasa Skou hanya menandai masa depan, menganut kala futur, dan penandanya menggunakan reduplikasi verba. Penanda aspek bahasa Skou, yaitu dengan reduplikasi, bersesuaian dengan pronomina persona, dan posisinya di belakang verba. Bahasa Skou sebagai salah satu bahasa yang memarkahi modus dan temporal secara perifrastis. Kata kunci: Skou, numeralia, pronomina, kala, aspek, modus